Efektivitas Penerapan Restorative Justice dalam Sistem Peradilan Pidana Anak di Indonesia - rahmiati (Universitas Tangerang Raya, 2024)
The restorative justice approach in the juvenile criminal justice system in Indonesia is an effort to create more humane justice by restoring relationships between perpetrators, victims and society. This study aims to analyze the effectiveness of implementing restorative justice in the juvenile criminal justice system in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The research method used is a normative and empirical juridical approach by examining primary and secondary legal data, as well as interviews with law enforcement officials.The research results show that restorative justice has a positive impact in reducing the negative impacts of the justice process on children, such as stigmatization and barriers to social reintegration. However, its effectiveness is still hampered by a lack of understanding of law enforcement officials, a lack of supporting facilities, and low community involvement. To improve the implementation of restorative justice, intensive training is needed for law enforcement officers, strengthening the role of community institutions, as well as outreach to victims and the community regarding the benefits of this approach. It is hoped that this research can become a reference in developing policies that are more effective and oriented towards child protection in the criminal justice system in Indonesia.